COVID‐19 severity in kidney transplant recipients is similar to nontransplant patients with similar comorbidities. Issue 3 (4th January 2021) - Chavarot, Nathalie; Gueguen, Juliette; Bonnet, Guillaume; Jdidou, Mariam; Trimaille, Antonin; Burger, Carole; Amrouche, Lucile; Weizman, Orianne; Pommier, Thibaut; Aubert, Olivier; Celier, Joffrey; Sberro‐Soussan, Rebecca; et al.
Abstract : Higher rates of severe COVID‐19 have been reported in kidney transplant recipients (KTRs) compared to nontransplant patients. We aimed to determine if poorer outcomes were specifically related to chronic immunosuppression or underlying comorbidities. We used a 1:1 propensity score‐matching method to compare survival and severe disease‐free survival (defined as death and/or need for intensive care unit [ICU]) incidence in hospitalized KTRs and nontransplant control patients between February 26 and May 22, 2020. Patients were matched for risk factors of severe COVID‐19: age, sex, body mass index, diabetes mellitus, preexisting cardiopathy, chronic lung disease, and basal renal function. We included 100 KTRs (median age [interquartile range (IQR)]) 64.7 years (55.3–73.1) in three French transplant centers. After a median follow‐up of 13 days (7–30), transfer to ICU was required for 34 patients (34%) and death occurred in 26 patients (26%). Overall, 43 patients (43%) developed a severe disease during a median follow‐up of 8.5 days (2–14). Propensity score matching to a large French cohort of 2017 patients hospitalized in 24 centers, revealed that survival was similar between KTRs and matched nontransplant patients with respective 30‐day survival of 62.9% and 71% ( p  = .38) and severe disease‐free 30‐day survival of 50.6% and 47.5% ( p  = .91). These findings suggest that severity of COVID‐19 in KTRs is related to their associated comorbidities and not to chronic immunosuppression. Abstract : Kidney transplant recipients matched to nontransplant patients for severe COVID‐19 risk factors present similar survival and incidence of severe COVID‐19, suggesting that chronic immunosuppression is not associated with the severity of COVID‐19.